Urban Debt, Neoliberalism and the Politics of the Commons. (May 2015) - Parr, Adrian
The rural/metropolitan/wilderness hybrid central to urban shrinkage directly challenges a commonly held belief that a city consists of a dense concentration of people living in a limited geographical area, one where the primary means of production is non-agricultural. In addition, the urban condition of shrinkage tests the dominant current of growth management that has guided urban design, development, and land use. In this essay we will explore how this hybrid presents an alternative to the production and realization of surplus value that predominates throughout the contemporary landscape of neoliberal planetary urbanization. It will be argued that this process of urbanization is premised upon modalities of urban commoning, or practices that bring a variety of social and environmental struggles into relationship with each other, dismantling the apparatuses of capture that bring land-use and the collective energies animating available land under the control of capital.